Implementation Of Quality Control In The Crab Production Process - Azmi, Indah Fauqo; Siti Saroh; Chanafi, Ainul (International Journal of Entrepreneur and Business Administration, 2024)
The purpose of this study is to determine the steps in PT. Manage Mina Laut's production process and to put quality control measures in place for the procedure. Qualitative research is the name given to this type of study. Three techniques were employed to acquire the data: observation, interviews, and documentation. One kind of data analysis used in this study is the interactive model. The results of research indicate that PT. Manage Mina Laut takes crab from fishermen who harvest it while it is still fresh and of very good quality. The company then processes these raw materials effectively to produce high quality goods. PT. Manage Mina Laut consistently upholds the quality of the goods they produce. Before the product is sent to the customer, quality control goes through several verification stages in the production process, starting with the selection of fresh and high quality raw materials (off-line quality control). (on-line quality control). PT. Kelola Mina Laut has carried out production processes and quality control in accordance with relevant protocols.